USE OF VIRTUAL EDUCATIONAL COMPLEXES IN PROFESSIONAL TRAINING OF QUALIFIED WORKERS (Innovative professional education, 2024)
Face-to-face training is undoubtedly valuable in many industries, but virtual learning has advantages that should be considered when training skilled workers. Virtual learning complexes are a useful tool if the educational process is organized in a virtual or simulated environment, when students and teachers are located in different places. It has been established that virtual learning can be conducted both in person and remotely.
Keywords: vocational education, virtual training complex (VTC), educational content, skilled worker, professional training